Polycyclic Aromatic Hydrocarbons and Potentially Toxic Elements in Soils of the Vicinity of the Bulgarian Antarctic Station “St. Kliment Ohridski” (Antarctic Peninsula) - Abakumov, Evgeny; Nizamutdinov, Timur; Yaneva, Rossitsa; Zhiyanski, Miglena (Frontiers in Environmental Science, 2021)
The investigation conducted was dialed to quantitative and qualitative evaluation of 15 priority polycyclic aromatic hydrocarbons (PAHs) and Potentially Toxic Elements (Cu, Pb, Zn, Cd, Ni and Cr) is soils and cryoconites on “St. Kliment Ohridski” Antarctic station territory and its vicinities. Estimation of benzo(a)pyrene (BaP) – equivalents, PAHs and different PAHs isomer pair ratios were used for identification of general toxicity, nature and origin of individual PAHs and their groups. Total concentrations of PAHs in BaP – equivalents showed, that ∑15PAH of all selected points was higher than the threshold concentration (20 μg×kg-1 - Russian environmental legislation) for benzo(a)pyrene. Different PAHs isomer ratios showed the natural (petrogenic) source of PAHs at all soils examples (except Cryosol Toxic Transportic). The maximum content among potentially toxic elements was recorded for Zn (75.7 mg×kg-1 at L26), the minimum for Cd (0.201 mg×kg-1 at L1A). Average concentrations of potentially toxic elements are generally lower compared to the results of previous studies. Application of Igeo index, characterizes the majority of the studied soils as unpolluted or practically unpolluted. Data obtained indicates that there is no current critical anthropogenic load on the environmental components of the landscapes investigated.